The Implementation of the Right to Education in Indonesia - Manan, Munafrizal (Indonesia Law Review, 2015)
This article discusses the implementation of the right to education in Indonesia. It uses human rights and historical approaches. Human rights approach is used to describe international human rights instruments on the guarantee of the right to education that is applied universally. This approach is also dealing with international human rights instrument on the right to education that has been ratified by Indonesia as well as national regulation instruments on the right to education applied in Indonesia. Historical approach highlights the role of Indonesian governments in education sector after the Independence Day, especially regarding the implementation of the right to education. The discussion focuses on the development that has been achieved and the difficultythat has been faced in the implementation of the right to education. Despite there have been significant progresses achieved in implementing the right to education, the Indonesian governments remain facing the difficulty to fulfil the right to education for the entire of Indonesian citizens. However, in the middle of such a difficulty, it raises a creative idea and concrete action from civil society in terms of providing education service for marginalized and indigenous peoples.